Enhancing aromatics and olefins yields in thermo-catalytic pyrolysis of LDPE over zeolites: Role of staged catalysis and acid site density of HZSM-5. (15th April 2022) - Inayat, Amer; Inayat, Alexandra; Schwieger, Wilhelm; Sokolova, Barbora; Lestinsky, Pavel
Graphical abstract: Highlights: Pyrolysis of LDPE over HZSM-5 catalysts is carried out in one- and two-stage rigs. Influence of operating parameters and catalyst acidity on product yields is studied. Higher acid density in HZSM-5 favors aromatization, while lower favors olefination. Product selectivity can be tuned by decoupling thermal and thermo-catalytic steps. Abstract: The present work deals with the thermo-catalytic pyrolysis of LDPE (low-density polyethylene) in lab-scale one- and two-stage test rigs over HZSM-5 catalysts featuring different acid site densities. In the first part of this work, the influence of catalyst-to-feed ratio and temperature (in conjunction with the acid site density of HZSM-5) on the product distribution was studied with an aim to identify the optimum operating conditions for the enhanced production of aromatics and light olefins. For this purpose, one-stage thermo-catalytic pyrolysis was performed in which catalysts were mixed with LDPE pellets for in-situ catalysis. In the one-stage catalytic pyrolysis, the catalyst sample with the highest acid site density gave the highest concentration of aromatics (ca. 55%) in the pyrolysis oil with a mono-aromatics fraction of over 50% that consisted mainly of BTEX (benzene, toluene, ethylbenzene and xylenes) compounds. The highest C2 -C4 olefins concentration (ca. 65%) in the pyrolysis gas was obtained when the sample with the lowest acid site density was used. In the two-stage catalytic pyrolysis ( ex-situ catalysis), the concentration of aromatics in the pyrolysis oil reached over 77% with a mono-aromatics fraction of ca. 72% that contained mainly BTEX compounds, when the most acidic catalyst was used. When the catalyst with the lowest number of strong acid sites was employed, the high content of C2 -C4 olefins in the pyrolysis gas remained almost independent of the reactor configuration. These findings might provide important new insights for the chemical recycling of plastic wastes.